A Survey on Maximum Power Point Tracking Methods in Photovoltaic Power Systems - Sobhan Dorahaki (Institute of Advanced Engineering and Science, 2015)
One of the most important issues associated with photovoltaic systems is receiving maximum power and tracking maximum power point. Hence, researchers have proposed numerous methods in recent years. The first step toward selecting a useful method is recognizing algorithms, methodology and advantages of each method. In this study MPPT methods are deeply investigated. For this purpose, first off, equations governing photovoltaic systems are explicated. Then, nonlinear behavior of photovoltaic cells is demonstrated by simulation. Finally, different methods of MPPT and their advantages are mentioned.